Analisis Integrasi Angkutan Kota sebagai Feeder Angkutan Bus Trans Mamminasata Berdasarkan Tujuan dan Sebaran Pergerakan - Kasim, Muhammad Ridha; Jihad, Ahmad (Jurnal Kridatama Sains dan Teknologi, 2024)
The performance of public transportation and transit systems is highly dependent on the connection between the beginning and end of a journey by public transportation. A good multimodal integration approach will create connections between the main mode and other modes, thereby reducing travel time and distance. In an effort to improve services to the public, especially public transport users, new bus stops or stopping places can be planned as legal places for passengers to board and alight. The aim of this research is to determine the travel characteristics of Teman Bus passengers in terms of the purpose of movement and origin and destination of movement and to find out the recommended locations for additional bus stops/stop places for the integration of Teman Bus and City Transportation based on the purpose of movement and origin and destination of passenger movements. The analytical method used is descriptive statistical analysis and analysis of the distribution of stops based on passenger boarding and dropping points. The results of the research show that there are several alternative bus stop developments that can be carried out in the type of land use for trade and services for economic activity purposes and the type of land use for education for the purpose of cultural activities.